A HR-XPS study of the formation of h-BN on Ni(111) from the two precursors, ammonia borane and borazine - Bachmann, Philipp; Düll, Fabian; Späth, Florian; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2018)
Together with borazine, ammonia borane is a prominent precursor molecule for the formation of hexagonal boron nitride, which is of high interest as a 2D-material and graphene analog. Ammonia borane is also a possible solid hydrogen carrier for renewable energies with high storage density. Using X-ray photoelectron spectroscopy and temperature-programmed desorption, we investigated low-temperature adsorption and dehydrogenation during heating of borazine and ammonia borane on Ni(111) to form h-BN. For borazine, we observe the formation of disordered boron nitride above 300 K, which starts to form hexagonal boron nitride above 600 K. Ammonia borane shows multiple dehydrogenation steps at the boron and nitrogen atoms up to 300 K. This results in various BHxNHy species, including borazine-like intermediates, before the formation of disordered boron nitride and finally hexagonal boron nitride, analogous to the borazine decomposition. Published by AIP Publishing.

Back Cover: Energy Storage in Strained Organic Molecules: (Spectro)Electrochemical Characterization of Norbornadiene and Quadricyclane (ChemSusChem 12/2016) - Brummel, Olaf; Besold, Daniel; Döpper, Tibor; Wu, Yanlin; Bochmann, Sebastian; Lazzari, Federica; Waidhas, Fabian; Bauer, Udo; Bachmann, Philipp; Papp, Christian; Steinrück, Hans-Peter; Görling, Andreas; et al. (ChemSusChem, 2016)
Keywords: infrared spectroscopy; norbornadiene; quadricyclane; spectroelectrochemistry; voltammetry

Bimetallic Pd-Pt alloy nanocluster arrays on graphene/Rh(111): formation, stability, and dynamics - Düll, Fabian; Bauer, Udo; Späth, Florian; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Papp, Christian (Physical Chemistry Chemical Physics, 2018)
Alloy catalysts have, in many cases, superior properties compared to their single metal counterparts. To gain deeper insights, we used graphene-supported bimetallic nanocluster arrays as a model system. We investigated the site occupation and the dynamic behavior of the metal distribution during adsorption and thermal treatment of CO layers on PdPt alloy nanocluster arrays supported on the graphene/Rh(111) Moire. We find that the adsorption of CO combined with heating to 550 K leads to a rearrangement of the surface atoms, resulting in all the edge sites of the nanoclusters being occupied by Pd atoms. At the same time, Pt gets enriched at the surface.

Catalytically Triggered Energy Release from Strained Organic Molecules: The Surface Chemistry of Quadricyclane and Norbornadiene on Pt(111) - Bauer, Udo; Mohr, Susanne; Döpper, Tibor; Bachmann, Philipp; Späth, Florian; Düll, Fabian; Schwarz, Matthias; Brummel, Olaf; Fromm, Lukas; Pinkert, Ute; Görling, Andreas; Hirsch, Andreas; et al. (Chemistry - A European Journal, 2017)
We have investigated the surface chemistry of the polycyclic valence-isomer pair norbornadiene (NBD) and quadricyclane (QC) on Pt(111). The NBD/QC system is considered to be a prototype for energy storage in strained organic compounds. By using a multimethod approach, including UV photoelectron, high-resolution X-ray photoelectron, and IR reflection-absorption spectroscopic analysis and DFT calculations, we could unambiguously identify and differentiate between the two molecules in the multilayer phase, which implies that the energy-loaded QC molecule is stable in this state. Upon adsorption in the (sub)monolayer regime, the different spectroscopies yielded identical spectra for NBD and QC at 125 and 160K, when multilayer desorption takes place. This behavior is explained by a rapid cycloreversion of QC to NBD upon contact with the Pt surface. The NBD adsorbs in a η:η geometry with an agostic Pt-H interaction of the bridgehead CH subunit and the surface. Strong spectral changes are observed between 190 and 220K because the hydrogen atom that forms the agostic bond is broke. This reaction yields a norbornadienyl intermediate species that is stable up to approximately 380K. At higher temperatures, the molecule dehydrogenates and decomposes into smaller carbonaceous fragment
Keywords: Catalysis; DFT calculations; IR spectroscopy; Photoelectron spectroscopy; Surfaces and interfaces

Controlled Catalytic Energy Release of the Norbornadiene/Quadricyclane Molecular Solar Thermal Energy Storage System on Ni(111) - Bauer, Udo; Fromm, Lukas; Weiß, Cornelius; Bachmann, Philipp; Späth, Florian; Düll, Fabian; Steinhauer, Johann; Hieringer, Wolfgang; Görling, Andreas; Hirsch, Andreas; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2019)

Dehydrogenation of the liquid organic hydrogen carrier system 2-methylindole/2-methylindoline/2-methyloctahydroindole on Pt(111) - Bachmann, Philipp; Steinhauer, Johann; Späth, Florian; Düll, Fabian; Bauer, Udo; Eschenbacher, Roman; Hemauer, Felix; Scheuermeyer, Marlene; Bösmann, Andreas; Büttner, Miriam; Neiß, Christian; Görling, Andreas; et al. (Journal of Chemical Physics, 2019)
Among other N-heterocycles, indole and its substituted derivatives, such as methylindoles, are considered promising Liquid Organic Hydrogen Carriers (LOHCs) for the storage of renewable energy. We used X-ray photoelectron spectroscopy (XPS), temperature programmed desorption (TPD), and density-functional theory (DFT) to investigate the low temperature adsorption and consecutive dehydrogenation reaction during heating of 2-methylindole, 2-methylindoline, and 2-methyloctahydroindole on Pt(111) and their viability as the LOHC system. In the photoemission experiments, for all Hx-2-methylindoles, we find deprotonation at the NH bond starting between 240 and 300 K, resulting in a 2-methylindolide species. Simultaneously or before this reaction step, the dehydrogenation of 2-methyloctahydroindole via 2-methylindoline and 2-methylindole intermediates is observed. For 2-methyloctahydroindole, we also find π-allyl intermediates above 230 K. Starting at ∼390 K, decomposition of the remaining 2-methylindolide species takes place under the conditions of our surface science experiments. DFT calculations give insight into the relative energies of the various species, reaction intermediates, and their isomers both in the gas phase and on the Pt(111) surface.
CRIS-Team Scopus Importer:2019-10-22

Dehydrogenation of the Liquid Organic Hydrogen Carrier System Indole/Indoline/Octahydroindole on Pt(111) - Bachmann, Philipp; Schwarz, Matthias; Steinhauer, Johann; Späth, Florian; Düll, Fabian; Bauer, Udo; Nascimento Silva, Thais; Mohr, Susanne; Hohner, Chantal; Scheuermeyer, Marlene; Wasserscheid, Peter; Libuda, Jörg; et al. (Journal of Physical Chemistry C, 2018)
Indole derivatives are considered as promising liquid organic hydrogen carriers for renewable energy storage. Using X-ray photoelectron spectroscopy, temperature-programmed desorption, and infrared reflection absorption spectroscopy, we investigated low-temperature adsorption and dehydrogenation during heating of indole, indoline, and octahydroindole on Pt(111). For all three molecules, we find deprotonation of the NH bond above 270 K, accompanied with dehydrogenation of indoline and octahydroindole via an indole intermediate, resulting in an indolide species above 300 K. For octahydroindole, we also find a side reaction yielding small amounts of a pi-allyl species between 170 and 450 K. Above 450 K, decomposition of the remaining indolide species takes place.

Energy Storage in Strained Organic Molecules: (Spectro)Electrochemical Characterization of Norbornadiene and Quadricyclane - Brummel, Olaf; Besold, Daniel; Döpper, Tibor; Wu, Yanlin; Bochmann, Sebastian; Lazzari, Federica; Waidhas, Fabian; Bauer, Udo; Bachmann, Philipp; Papp, Christian; Steinrück, Hans-Peter; Görling, Andreas; et al. (Chemsuschem, 2016)
We have investigated the electrochemically triggered cycloreversion of quadricyclane (QC) to norbornadiene (NBD), a system that holds the potential to combine both energy storage and conversion in a single molecule. Unambiguous voltammetric traces are obtained for pure NBD and pure QC, the latter a strained polycyclic isomer of the former. The difference in redox potentials is smaller than the energy difference between the neutral molecules. This is owing to a significant energy difference between the corresponding radical cations, as demonstrated by density functional theory (DFT) calculations. The vibrational modes of each pure compound are characterized experimentally in the fingerprint region and identified by DFT methods. Thermal and electrochemical transformations of NBD and QC are monitored insitu by IR spectroelectrochemical methods. The kinetics of the cycloreversion of QC to NBD, which is catalyzed by oxidizing equivalents, can be controlled by an applied electrode potential, which implies the ability to adjust in real time the release of thermal power stored in QC.
Keywords: Infrared spectroscopy; Norbornadiene; Quadricyclane; Spectroelectrochemistry; Voltammetry

Ethylene: Its adsorption, reaction, and coking on Pt/h-BN/Rh(111) nanocluster arrays - Düll, Fabian; Steinhauer, Johann; Späth, Florian; Bauer, Udo; Bachmann, Philipp; Steinrück, Hans-Peter; Wickert, Sandra; Denecke, Reinhard; Papp, Christian (Journal of Chemical Physics, 2020)
We present well-ordered Pt nanocluster arrays supported on the h-BN/Rh(111) Moiré as a model system for an ethylene dehydrogenation catalyst. Thereby, the h-BN nanomesh serves as a chemically inert eggbox-like template for clusters with a narrow size distribution. The thermal evolution of ethylene is investigated by synchrotron-based high-resolution in situ x-ray photoelectron spectroscopy on the Pt nanoclusters. We compare our results with data on Pt(111) and Pt(355). Interestingly, the Pt nanoclusters and Pt(355) behave very similarly. Both open a new reaction pathway via vinylidene in addition to the route via ethylidyne known for Pt(111). Due to the importance of coking in ethylene dehydrogenation on Pt catalysts, we also studied C2H4 adsorption and decomposition on carbon precovered Pt nanoclusters. While the amount of adsorbed ethylene decreases linearly with the carbon coverage, we found that edge sites are more affected than facet sites and that the vinylidene reaction pathway is effectively suppressed by carbon residues.
CRIS-Team Scopus Importer:2020-06-26

Growth and stability of Pt nanoclusters from 1 to 50 atoms on h-BN/Rh(111) - Düll, Fabian; Meusel, Manuel; Späth, Florian; Schötz, Simon; Bauer, Udo; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Bayer, Andreas; Papp, Christian (Physical Chemistry Chemical Physics, 2019)
The h-BN nanomesh on Rh(111) is used as eggbox-like template for the formation of arrays of Pt nanoclusters with a narrow size distribution. Nanoclusters with sizes from 1 up to 50 atoms are prepared simultaneously in a wedge-like structure by depositing a coverage gradient on the h-BN nanomesh, and thus can be investigated under identical conditions. We studied the preparation and properties of these Pt nanoclusters of different size in situ by high-resolution X-ray photoelectron spectroscopy and scanning tunneling microscopy. For a Pt coverage of 0.1 ML, all pores of the h-BN nanomesh are filled with nanoclusters with a remarkably uniform cluster size of ≈12 Pt atoms per pore, and high stability up to 400 K. Above 0.2 ML Pt, the clusters are less stable. The coverage dependent analysis shows that for Pt coverages below 0.1 ML, the number of nanoclusters is smaller - and the number of empty pores higher - than expected for a simple hit and stick mechanism. We assign this behavior to an initially higher mobility of the Pt atoms in a hot precursor state.
CRIS-Team Scopus Importer:2019-10-11

Hydrogenation and hydrogen intercalation of hexagonal boron nitride on Ni(111): reactivity and electronic structure - Späth, Florian; Gebhardt, Julian; Düll, Fabian; Bauer, Udo; Bachmann, Philipp; Gleichweit, Christoph; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (2D Materials, 2017)
We investigate the reactivity of hexagonal boron nitride (h-BN) on a Ni(1 1 1) single crystal towards atomic hydrogen over a wide exposure range. Near edge x-ray absorption fine structure and x-ray photoelectron spectroscopy (XPS) show that for low hydrogen exposures hydrogenation of the h-BN sheet is found. In contrast, intercalation of hydrogen between h-BN and the Ni(1 1 1) substrate occurs for high exposures. For intermediate regimes, a mixture of intercalation and hydrogenation is observed. From temperature-programmed desorption and temperature-programmed XPS experiments, we conclude that the hydrogen covalently bound to h-BN is rather stable with a desorption temperature of 600 K, while intercalated hydrogen is desorbing already at 390 K. Further insight into the structural arrangements and the thermodynamics of the system is obtained by comparing our experimental results with extensive density-functional theory calculations. Together with ultraviolet photoelectron spectroscopy measurements, the calculations provide detailed insight into the influence of hydrogenation on the electronic structure of h-BN.
Keywords: hexagonal boron nitride; hydrogenation; intercalation; electronic structure

Model Catalytic Studies of Liquid Organic Hydrogen Carriers: Indole/Indoline/Octahydroindole on Ni(111) - Steinhauer, Johann; Bachmann, Philipp; Freiberger, Marie; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2020)
N-heterocycles belong to the class of so-called liquid organic hydrogen carriers (LOHCs), which have been identified as suitable materials for chemical hydrogen storage due to favorable hydrogen storage capacity and reaction kinetics. In this contribution, we focus on the dehydrogenation reaction of hydrogen-rich octahydroindole, its dehydrogenation intermediate indoline, and hydrogen-lean indole. Octahydroindole has a hydrogen storage capacity of 6.4 wt %, and indoline has 1.7 wt %. We investigated the mechanism of the temperature-induced dehydrogenation of the three compounds after adsorption on Ni(111) at low temperatures. Nickel is attractive as an effective and low-priced dehydrogenation catalyst, which potentially could replace more expensive Pt and Pd in industrial applications. We compare the obtained results with our previous work on Pt(111) for the same LOHC system and for N-ethylcarbazole/H-12-N-ethylcarbazole. A comprehensive understanding of the reaction mechanism was obtained by combining high-resolution X-ray photoelectron spectroscopy with temperature-programmed desorption lab experiments. For all three compounds, we find dehydrogenation at the nitrogen atom above 270 K (indole, >= 130 K; indoline, >240 K; octahydroindole, >270 K). For indoline and octahydroindole, we observe simultaneous dehydrogenation at the carbon atoms, resulting in an indolide surface species. For octahydroindole, small amounts of side products and decomposition products are observed throughout the reaction pathway. Above 380 K, the indolide species decomposes into fragments for all three compounds.
CRIS-Team WoS Importer:2020-11-27

Model Catalytic Studies of Novel Liquid Organic Hydrogen Carriers: Indole, Indoline and Octahydroindole on Pt(111) - Schwarz, Matthias; Bachmann, Philipp; Nascimento Silva, Thais; Mohr, Susanne; Scheuermeyer, Marlene; Späth, Florian; Bauer, Udo; Düll, Fabian; Steinhauer, Johann; Hohner, Chantal; Döpper, Tibor; Noei, Heshmat; et al. (Chemistry - A European Journal, 2017)
Indole derivatives were recently proposed as potential liquid organic hydrogen carriers (LOHC) for storage of renewable energies. In this work, we have investigated the adsorption, dehydrogenation and degradation mechanisms in the indole/indoline/octahydroindole system on Pt(111). We have combined infrared reflection absorption spectroscopy (IRAS), X-ray photoelectron spectroscopy (XPS) and DFT calculations. Indole multilayers show a crystallization transition at 200 K, in which the molecules adopt a strongly tilted orientation, before the multilayer desorbs at 220 K. For indoline, a less pronounced restructuring transition occurs at 150 K and multilayer desorption is observed at 200 K. Octahydroindole multilayers desorb already at 185 K, without any indication for restructuring. Adsorbed monolayers of all three compounds are stable up to room temperature and undergo deprotonation at the NH bond above 300 K. For indoline, the reaction is followed by partial dehydrogenation at the 5-membered ring, leading to the formation of a flat-lying di-sigma-indolide in the temperature range from 330-390 K. Noteworthy, the same surface intermediate is formed from indole. In contrast, the reaction of octahydroindole with Pt(111) leads to the formation of a different intermediate, which originates from partial dehydrogenation of the 6-membered ring. Above 390 K, all three compounds again form the same strongly dehydrogenated and partially decomposed surface species.
Keywords: density functional theory; infrared reflection absorption spectroscopy; liquid organic hydrogen carrier; octahydroindole; X-ray photoelectron spectroscopy

Model Catalytic Studies of the LOHC System 2,2′-Bipiperidine/2,2′-Bipyridine on Ni(111) - Steinhauer, Johann; Bachmann, Philipp; Bauer, Udo; Düll, Fabian; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2021)
N-heterocyclic compounds such as octahydroindole and dodecahydro-N-ethylcarbazole have been proposed as suitable liquid organic hydrogen carriers for chemical hydrogen storage. Following these studies, we focused on hydrogen-rich 2,2′-bipiperidine with a hydrogen storage capacity of 7.1 wt % and hydrogen-lean 2,2′-bipyridine. Both were adsorbed on Ni(111), and the temperature-induced reaction mechanism and decomposition were studied. The reaction was investigated using synchrotron-based XPS, NEXAFS, and TPD experiments. Upon adsorption, the formation of a flat-lying chemisorbed layer is observed. Above 370 K, 2,2′-bipyridine is dehydrogenated in the α-position to the nitrogen atoms to form an α-2,2′-bipyridyl species with a tilted adsorption geometry. The hydrogen-rich 2,2′-bipiperidine is partially dehydrogenated above 180 K and deprotonated at the nitrogen atoms above 250 K. Above 320 K, α-2,2′-bipyridyl is formed, which is accompanied by a byproduct that is partially dehydrogenated at the carbon atoms. Above 400 K, we observe the decomposition of the α-2,2′-bipyridyl species.
CRIS-Team Scopus Importer:2021-05-14

Pt Nanoclusters Sandwiched between Hexagonal Boron Nitride and Nanographene as van der Waals Heterostructures for Optoelectronics - Düll, Fabian; Freiberger, Eva Marie; Bachmann, Philipp; Steinhauer, Johann; Papp, Christian (ACS Applied Nano Materials, 2019)
We report on the formation of nanoscopic heterostructures composed of the semimetal graphene, the metal Pt, and the insulator hexagonal boron nitride (h-BN). Both graphene and h-BN are chemically inert two-dimensional materials with similar geometric but different electronic properties. Between these materials, a Pt nanoparticle array was encapsulated. Thereby, the h-BN/Rh(111) nanomesh served as a template for a well-ordered array of Pt nanoclusters, which were overgrown with graphene, forming single-crystal nanoheterostructures. We investigated this process in situ by high-resolution, synchrotron-radiation-based X-ray photoelectron spectroscopy and near-edge X-ray absorption fine structure. The nanographene layers proved tight against CO under the tested conditions. These nanoheterostructures could find possible application in optoelectronics or as a data storage material. At the same time, our approach represents a new route for the synthesis of nanographene.
CRIS-Team Scopus Importer:2019-11-22
Keywords: hexagonal boron nitride; nanographene; Pt nanoclusters

Reaction of Hydrogen and Oxygen on h-BN - Späth, Florian; Steinhauer, Johann; Düll, Fabian; Bauer, Udo; Bachmann, Philipp; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2020)
We report the reversible functionalization of hexagonal boron nitride (h-BN) on Ni(111) with a molecular oxygen species and atomic hydrogen, as studied by high-resolution X-ray photoelectron spectroscopy, ultraviolet photoelectron spectroscopy, and near-edge X-ray absorption fine structure. As a first step, we prepare oxygen-functionalized h-BN by exposure to a supersonic beam of molecular oxygen. Subsequent exposure to atomic hydrogen leads to complete removal of the oxygen species and the formation of hydrogen-functionalized h-BN. In turn, this hydrogen-functionalized h-BN can be reconverted to oxygen-functionalized h-BN by exposure to the supersonic oxygen beam. This reaction occurs at a lower rate as the initial functionalization of pristine h-BN with oxygen. We further demonstrate that the core levels and valence bands of h-BN can be shifted at will between the boundaries obtained for the purely oxygen- and hydrogen-functionalized h-BN layers.
CRIS-Team WoS Importer:2020-09-18

Reactivity and Passivation of Fe Nanoclusters on h-BN/Rh(111) - Waleska, Natalie; Düll, Fabian; Bachmann, Philipp; Hemauer, Felix; Steinhauer, Johann; Papp, Christian (Chemistry - A European Journal, 2021)
The reactivity of iron nanocluster arrays on h-BN/Rh(111) was studied using in situ high-resolution X-ray photoelectron spectroscopy. The morphology and reactivity of the iron nanoclusters (Fe-NCs) were investigated by CO adsorption. On-top and hollow/edge sites were determined to be the available adsorption sites on the as-prepared Fe-NCs and CO dissociation was observed at 300 K. C- and O-precovered Fe-NCs showed no catalytic activity towards CO dissociation because the hollow/edge sites were blocked by the C and O atoms. Therefore, these adsorption sites were identified to be the most active sites of the Fe-NCs.
CRIS-Team Scopus Importer:2021-09-10
Keywords: heterogeneous catalysis; iron; model catalysis; nanocluster array; XPS

Reactivity of CO on Sulfur-Passivated Graphene-Supported Palladium Nanocluster Arrays - Düll, Fabian; Späth, Florian; Bachmann, Philipp; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2017)
Nanocluster arrays on graphene are suitable model systems for catalysis. We use this model system to study sulfur poisoning, which is a major deactivation process of heterogeneous catalysts. Using high-resolution X-ray photoelectron spectroscopy, we investigated the adsorption and desorption of CO on sulfur-poisoned graphene-supported palladium nanoparticles. We find that sulfur blocks CO adsorption sites, with hollow sites being most affected. From the unchanged desorption temperatures, we conclude that the Pd-CO bond strength is not altered by co-adsorbed sulfur. The degree of site blocking compared to the amount of sulfur indicates that the palladium nanoparticle surface is dominated by (111) and (100) facets.

Reactivity of CO on Sulfur-Passivated Graphene-Supported Platinum Nanocluster Arrays - Düll, Fabian; Späth, Florian; Bauer, Udo; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2018)

Regeneration of LOHC dehydrogenation catalysts: In-situ IR spectroscopy on single crystals, model catalysts, and real catalysts from UHV to near ambient pressure - Amende, Maximilian; Kaftan, Andre; Bachmann, Philipp; Brehmer, Richard; Preuster, Patrick; Koch, Marcus; Wasserscheid, Peter; Libuda, Jörg (Applied Surface Science, 2016)
The Liquid Organic Hydrogen Carrier (LOHC) concept offers an efficient route to store hydrogen using organic compounds that are reversibly hydrogenated and dehydrogenated. One important challenge towards application of the LOHC technology at a larger scale is to minimize degradation of Pt-based dehydrogenation catalysts during long-term operation. Herein, we investigate the regeneration of Pt/alumina catalysts poisoned by LOHC degradation. We combine ultrahigh vacuum (UHV) studies on Pt(111), investigations on well-defined Pt/AlO model catalysts, and near-ambient pressure (NAP) measurements on real core-shell Pt/AlO catalyst pellets. The catalysts were purposely poisoned by reaction with the LOHC perhydro-dibenzyltoluene (H18-MSH) and with dicyclohexylmethane (DCHM) as a simpler model compound. We focus on oxidative regeneration under conditions that may be applied in real dehydrogenation reactors. The degree of poisoning and regeneration under oxidative reaction conditions was quantified using CO as a probe molecule and measured by infrared reflection-absorption spectroscopy (IRAS) and diffuse reflectance Fourier transform IR spectroscopy (DRIFTS) for planar model systems and real catalysts, respectively. We find that regeneration strongly depends on the composition of the catalyst surface. While the clean surface of a poisoned Pt(111) single crystal is fully restored upon thermal treatment in oxygen up to 700 K, contaminated Pt/AlO model catalyst and core-shell pellet were only partially restored under the applied reaction conditions. Whereas partial regeneration on facet-like sites on supported catalysts is more facile than on Pt(111), carbonaceous deposits adsorbed at low-coordinated defect sites impede full regeneration of the Pt/AlO catalysts.
Keywords: Infrared spectroscopy; Liquid Organic Hydrogen Carrier; Materials gap; Model catalysis; Pressure gap; Real catalysis

Selective Oxygen and Hydrogen Functionalization of the h-BN/Rh(111) Nanomesh - Freiberger, Eva Marie; Späth, Florian; Bauer, Udo; Düll, Fabian; Bachmann, Philipp; Steinhauer, Johann; Hemauer, Felix; Waleska, Natalie; Schwaab, Valentin; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2021)
We present detailed studies on the covalent adsorption of molecular oxygen and atomic hydrogen on the hexagonal boron nitride (h-BN) nanomesh on Rh(111). The functionalization of this two-dimensional (2D) material was investigated under ultra-high vacuum conditions using synchrotron radiation-based in situ high-resolution X-ray photoelectron spectroscopy, temperature-programmed X-ray photoelectron spectroscopy and ultraviolet photoelectron spectroscopy. We are able to provide a deep insight into the adsorption behavior and thermal stability of oxygen and hydrogen on h-BN/Rh(111). Oxygen functionalization was achieved via a supersonic molecular beam while hydrogen functionalization was realized using an atomic hydrogen source. Adsorption of the respective species was observed to occur selectively in the pores of h-BN leading to spatially defined modification of the 2D layer. The adsorption of the observed molecular oxygen species was found to be an activated process that requires high-energy oxygen molecules. Upon heating to 700 K, oxygen functionalization was observed to be almost reversible except for small amounts of boron oxides evolving due to the reaction of oxygen with the 2D material. Hydrogen functionalization of h-BN/Rh(111) was fully reversed upon heating to about 640 K.
CRIS-Team WoS Importer:2021-08-20

Sulfur oxidation on graphene-supported platinum nanocluster arrays - Düll, Fabian; Schwaab, Valentin; Späth, Florian; Bauer, Udo; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Papp, Christian (Chemical Physics Letters, 2018)
Nanocluster arrays grown on a graphene Moire on Rh(1 1 1) are an excellent model system that can bridge the materials gap between single crystals and real catalysts. They feature different adsorption sites like edges, kinks, and facets, but are at the same time well-ordered with a small size distribution. Herein, we used platinum nanocluster arrays to investigate the oxidation of sulfur, which is a common catalyst poison, as a possible route to restore the catalyst. We studied the kinetics in a site-resolved manner with high-resolution XPS, despite the complex shape of the nanoparticles. Since SO3 and SO4 were the only observable SOx surface species, the reaction of S to SO was identified as the rate-determining step. As a secondary process, the displacement of sulfur from edge to facet sites caused by oxygen was observed.

Surface chemistry of 2,3-dibromosubstituted norbornadiene/quadricyclane as molecular solar thermal energy storage system on Ni(111) - Bauer, Udo; Fromm, Lukas; Weiß, Cornelius; Späth, Florian; Bachmann, Philipp; Düll, Fabian; Steinhauer, Johann; Matysik, Sabine; Pominov, Arkadii; Görling, Andreas; Hirsch, Andreas; Steinrück, Hans-Peter; et al. (Journal of Chemical Physics, 2019)
Dwindling fossil fuels force humanity to search for new energy production routes. Besides energy generation, its storage is a crucial aspect. One promising approach is to store energy from the sun chemically in strained organic molecules, so-called molecular solar thermal (MOST) systems, which can release the stored energy catalytically. A prototypical MOST system is norbornadiene/quadricyclane (NBD/QC) whose energy release and surface chemistry need to be understood. Besides important key parameters such as molecular weight, endergonic reaction profiles, and sufficient quantum yields, the position of the absorption onset of NBD is crucial to cover preferably a large range of sunlight's spectrum. For this purpose, one typically derivatizes NBD with electron-donating and/or electron-accepting substituents. To keep the model system simple enough to be investigated with photoemission techniques, we introduced bromine atoms at the 2,3-position of both compounds. We study the adsorption behavior, energy release, and surface chemistry on Ni(111) using high-resolution X-ray photoelectron spectroscopy (HR-XPS), UV photoelectron spectroscopy, and density functional theory calculations. Both Br 2 -NBD and Br 2 -QC partially dissociate on the surface at ∼120 K, with Br 2 -QC being more stable. Several stable adsorption geometries for intact and dissociated species were calculated, and the most stable structures are determined for both molecules. By temperature-programmed HR-XPS, we were able to observe the conversion of Br 2 -QC to Br 2 -NBD in situ at 170 K. The decomposition of Br 2 -NBD starts at 190 K when C-Br bond cleavage occurs and benzene and methylidene are formed. For Br 2 -QC, the cleavage already occurs at 130 K when cycloreversion to Br 2 -NBD sets in.
CRIS-Team Scopus Importer:2019-05-28

Surface Chemistry of the Molecular Solar Thermal Energy Storage System 2,3-Dicyano-Norbornadiene/Quadricyclane on Ni(111) - Hemauer, Felix; Bauer, Udo; Fromm, Lukas; Weiß, Cornelius; Leng, Andreas; Bachmann, Philipp; Düll, Fabian; Steinhauer, Johann; Schwaab, Valentin; Grzonka, Robert; Hirsch, Andreas; Görling, Andreas; et al. (ChemPhysChem, 2022)
Molecular solar thermal (MOST) systems are a promising approach for the introduction of sustainable energy storage solutions. We investigated the feasibility of the dicyano-substituted norbornadiene/quadricyclane molecule pair on Ni(111) for catalytic model studies. This derivatization is known to lead to a desired bathochromic shift of the absorption maximum of the parent compound. In our experiments further favorable properties were found: At low temperatures, both molecules adsorb intact without any dissociation. In situ temperature-programmed HR-XPS experiments reveal the conversion of (CN)(2)-quadricyclane to (CN)(2)-norbornadiene under energy release between 175 and 260 K. The absence of other surface species due to side reactions indicates full isomerization. Further heating leads to the decomposition of the molecular framework into smaller carbonaceous fragments above 290 K and finally to amorphous structures, carbide and nitride above 400 K. DFT calculations gave insights into the adsorption geometries. (CN)(2)-norbornadiene is expected to interact stronger with the surface, with flat configurations being favorable. (CN)(2)-quadricyclane exhibits smaller adsorption energies with negligible differences for flat and side-on geometries. Simulated XP spectra are in good agreement with experimental findings further supporting the specific spectroscopic fingerprints for both valence isomers.
CRIS-Team WoS Importer:2022-07-08

Surface Studies on the Energy Release of the MOST System 2-Carbethoxy-3-Phenyl-Norbornadiene/Quadricyclane (PENBD/PEQC) on Pt(111) and Ni(111) - Hemauer, Felix; Schwaab, Valentin; Freiberger, Eva Marie; Waleska, Natalie; Leng, Andreas; Weiß, Cornelius; Steinhauer, Johann; Düll, Fabian; Bachmann, Philipp; Hirsch, Andreas; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2023)
Novel energy-storage solutions are necessary for the transition from fossil to renewable energy sources. Auspicious candidates are so-called molecular solar thermal (MOST) systems. In our study, we investigate the surface chemistry of a derivatized norbornadiene/quadricyclane molecule pair. By using suitable push–pull substituents, a bathochromic shift of the absorption onset is achieved, allowing a greater overlap with the solar spectrum. Specifically, the adsorption and thermally induced reactions of 2-carbethoxy-3-phenyl-norbornadiene/quadricyclane are assessed on Pt(111) and Ni(111) as model catalyst surfaces by synchrotron radiation-based X-ray photoelectron spectroscopy (XPS). Comparison of the respective XP spectra enables the distinction of the energy-rich molecule from its energy-lean counterpart and allows qualitative information on the adsorption motifs to be derived. Monitoring the quantitative cycloreversion between 140 and 230 K spectroscopically demonstrates the release of the stored energy to be successfully triggered on Pt(111). Heating to above 300 K leads to fragmentation of the molecular framework. On Ni(111), no conversion of the energy-rich compound takes place. The individual decomposition pathways of the two isomers begin at 160 and 180 K, respectively. Pronounced desorption of almost the entire surface coverage only occurs for the energy-lean molecule on Ni(111) above 280 K; this suggests weakly bound species. The correlation between adsorption motif and desorption behavior is important for applications of MOST systems in heterogeneously catalyzed processes.
CRIS-Team Scopus Importer:2023-03-31
Keywords: catalysis; energy storage; MOST system; photoelectron spectroscopy; surface reactions